2021
DOI: 10.3390/antibiotics10080979
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant Klebsiella pneumoniae Causing Severe Infections in the Neuro-ICU

Abstract: The purpose of this study was the identification of genetic lineages and antimicrobial resistance (AMR) and virulence genes in Klebsiella pneumoniae isolates associated with severe infections in the neuro-ICU. Susceptibility to antimicrobials was determined using the Vitek-2 instrument. AMR and virulence genes, sequence types (STs), and capsular types were identified by PCR. Whole-genome sequencing was conducted on the Illumina MiSeq platform. It was shown that K. pneumoniae isolates of ST14K2, ST23K57, ST39K2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 61 publications
1
16
0
1
Order By: Relevance
“…In a recent study on Klebsiella spp. causing community-acquired infections, it has been described a positive rate of 28.2% and 61.5% for wabG and uge genes, respectively [37], while in other studies, the rates of positivity were close to 100% for both uge and wabG among virulent clones of K. pneumoniae [49,52]. Neither wabG nor uge were present in the isolates belonging to the K. oxytoca complex.…”
Section: Discussionmentioning
confidence: 81%
“…In a recent study on Klebsiella spp. causing community-acquired infections, it has been described a positive rate of 28.2% and 61.5% for wabG and uge genes, respectively [37], while in other studies, the rates of positivity were close to 100% for both uge and wabG among virulent clones of K. pneumoniae [49,52]. Neither wabG nor uge were present in the isolates belonging to the K. oxytoca complex.…”
Section: Discussionmentioning
confidence: 81%
“…In contrast, our ST307 K. pneumoniae clones did not feature any common virulence gene. Capsule typing showed that the ST307 K. pneumoniae isolates was associated with the KL102 capsular type, which has been described in severe infections ( 22 ). The CRACKLE-2 study ( 23 ) found that K. pneumoniae ST307 was the second most prevalent CPE (95% associated with bla KPC-2 ), after K. pneumoniae ST258, across 49 American hospitals between 2016 and 2017.…”
Section: Discussionmentioning
confidence: 85%
“…K. pneumoniae caused about 28% among the agents of nosocomial infections in neurosurgery ICU during the period from January 2014 to May 2019. The incidence rates of K. pneumoniae infections were 8.0 per 100 patient infections of the central nervous system, 4.3/100 of bloodstream infections, 26.3/100 of respiratory infections, and 25.3/100 of urinary tract infections [ 9 , 10 ]. A total of 545 K. pneumoniae clinical isolates were collected from 283 patients in this period, including those isolated from the respiratory system ( n = 271), urine ( n = 166), the nervous system ( n = 41), blood ( n = 36), surgical wounds ( n = 27), and other ( n = 4).…”
Section: Resultsmentioning
confidence: 99%
“…Beta-lactamase genes bla SHV , bla CTX-M , bla TEM , bla OXA-48 , bla KPC , bla VIM , bla IMP , and bla NDM , class 1 and 2 integrons, and porin protein gene ompK36 , as well as 8 genes associated with K. pneumoniae virulence, rmpA (hypermucoid phenotype regulator), aer (aerobactin), kfu (ferric absorption system), uge (uridine diphosphate-galacturonate-4-epimerase), wabG (glucosyltransferase), fimH (fimbria type I), allS and allR (allantoin regulon), were detected by PCR using specific primers as was described previously [ 10 ].…”
Section: Methodsmentioning
confidence: 99%